Precondition Model for Field Work Practices Based on Project-Based Learning to Improve Vocational School Stundents’ Competence and Readiness in Entrepreneurship, Fashion Design Expertise Program - Hidayah, Hanif Nurul (Universitas Negeri Semarang, 2020)
Vocational High School (SMK) is an educational institution that specifically aims to prepare students to be ready for work, either working independently or filling existing job vacancies. Appropriate learning can improve vocational students 'skills and vocational school students' readiness in entrepreneurship. This study aims to 1) produce a Precondition Model for Industrial Work Practices based on project-based learning to improve competency and work readiness of vocational school students in the Dressmaking expertise program. 2) to analyze the feasibility of the Preconditioned Industrial Work Practice Model based on project-based learning to improve the competence and work readiness of the Vocational School students in the Fashion Design expertise program 3) knowing the practicality of the Precondition Model for Industrial Work Practice based on project-based learning to improve competency and job readiness of vocational school students. Dressmaking expertise program Fashion. This type of research is development research (R&D) with a development model adapting to ADDIE development. The instruments used in this study were 1) Feasibility Assessment Sheet for the Precondition Model Model for Industrial Work Practice based on project-based learning 2) Practicality questionnaire for the Precondition Model for Industrial Work Practice based on a project-based learning 3) Evaluation sheet for evaluation of the effectiveness of project-based learning based on basic competency analyze the hemispheres in a product. The data analysis used in this study was (1) the scoring category to determine the level of feasibility of the Preconditioned Fieldwork Practices model based on project-based learning to improve the competence and readiness of vocational students in entrepreneurship in the Dressmaking expertise program. (2) to determine the level of practicality of the Preconditioning Practical Fieldwork model based on project-based learning using a Likert scale (3) N-Gain and the N-Gain difference test using the t-test, to determine the effectiveness of the Preconditioned Fieldwork Practices model based on project-based learning to improve the readiness of vocational high school students in entrepreneurship in the Dressmaking expertise program. The results of this study indicate that the assessment of the first validator and the second validator obtained criteria very worthy of use and based on the effectiveness test in the experimental class obtained effective and significant values to increase the readiness of junior high school students in entrepreneurship.